2010
DOI: 10.1007/s11295-010-0331-9
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting cork oak growth under dry conditions: local adaptation and contrasting additive genetic variance within populations

Abstract: Increased drought severity is expected in the Mediterranean Basin over the twenty-first century, but our understanding of the potential of most forest tree species to cope with it remains uncertain. In this study, (1) we examined the potential effects of long-term selection and the capacity to respond to future changes in selective pressures in three populations of cork oak (Quercus suber L.). For this purpose, we evaluated the response to dry conditions of 45 open-pollinated trees originating from populations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
34
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 66 publications
9
34
1
Order By: Relevance
“…Measurements of leaf traits (LS; SLA; δ 13 C; N mass ) adaptation in response to diverging climates Inter-population differences in LS, SLA and δ 13 C and a significant genotypeenvironment interaction for shoot growth were found.. Phenotypic correlation between the differences in shoot growth among years and the annual mean temperature is described.. Valiente et al, 2011 Common garden experiment with 3 populations (Morocco, Portugal, Spain) of 9-year-old plants.…”
Section: Ramirezmentioning
confidence: 97%
“…Measurements of leaf traits (LS; SLA; δ 13 C; N mass ) adaptation in response to diverging climates Inter-population differences in LS, SLA and δ 13 C and a significant genotypeenvironment interaction for shoot growth were found.. Phenotypic correlation between the differences in shoot growth among years and the annual mean temperature is described.. Valiente et al, 2011 Common garden experiment with 3 populations (Morocco, Portugal, Spain) of 9-year-old plants.…”
Section: Ramirezmentioning
confidence: 97%
“…Two plants per family were set in each block. Populations originated from sites in Morocco, Spain, and Portugal that have similar annual rainfall, but contrasting severity of the dry season (Ramirez-Valiente et al 2011). Briefly, there is a pattern of increasing drought severity and length toward southern sites.…”
Section: Common Gardenmentioning
confidence: 99%
“…Indeed, Gimeno et al (2008) pointed out that plasticity in this species is more important than adaptation and genetic differences among population in response to environmental stress. However, other studies have found a higher drought tolerance and lower SLA in Q. ilex and Q. suber seedlings from drier provenances , Ramírez-Valiente et al 2011. During the studied period, the most intense drought event occurred in 2012.…”
Section: Discussionmentioning
confidence: 58%
“…Ramírez-Valiente et al (2011) found that Q. suber populations from drier sites showed a higher growth potential. Several studies with other broadleaved tree species have also reported greater growth rates in those individuals from drier provenances (Savva et al 2007, Leland et al 2016.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 92%